„MIRROR EFFECT” AS A POLITICAL MARKETING PROBLEM - Самброс, А.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The connection between concept of “Mirror effect” and modern development level of political marketing technologies is studied. The impact of “Mirror effect”, that it makes on the process of development and use of political products is researched.